Knowledge Level of Smallholder Woman Farmers of Poultry Producer Company in Madhya Pradesh (Indian Journal of Extension Education, 2022)
The poultry producer companies provide trainings and extension services to their members. The present study was conducted in 2021-22 in Madhya Pradesh state to assess the impact of poultry Producer Company on knowledge level of smallholder women poultry farmers of company. Ex-post facto research design was used. Multistage sampling was done for the selection of respondents. Data was collected from randomly selected, 140 members and 140 non-members, through a structured interview schedule. Propensity score matching was applied at 0.2 tolerance level, to reduce extraneous variable effect and finally 96 members and 96 non-members respondents were selected for data analysis and interpretation of results. The majority of the members had medium to a high level of knowledge of poultry housing, brooding, litter management and feeding while medium to low level of knowledge of healthcare management, whereas, most non-members had a medium to low level of knowledge of poultry housing, litter management, feeding, and healthcare, and medium to high level of knowledge of brooding. There was a significant difference in knowledge of members and non-members at 0.1% level of significance regarding housing, litter management, and feeding and interpreted as poultry producer company had positive impact on knowledge of member poultry farmers.